Technological options for doubling farmers’ income in Rajasthan by 2022 scope, strategy and action plan - Yadav, O. P.; Singh, D. V.; Sharma, U. S. (Indian Farming, 2018)
The agro-climatic conditions of Rajasthan pose serious challenges in production of crops and livestock resulting in low productivity and lesser income of farmers. However, there exist certain strength and opportunities in agriculture sector of the State. This article examines both challenges and strengths of agriculture and allied activities in Rajasthan in enhancing net returns from farming through improved technological interventions in existing framework of policy and marketing. The analysis of data indicated that annual compound growth rate is highest in livestock sector (18%) followed by fisheries(11%), crop sector (4.7%) and forest sector (3.8%). There exists a tremendous scope not only to maintain this rate of growth but also to raise it further using an inclusive approach of increasing crop and livestock productivity through proper technological interventions,stabilizing prices of local commodities through appropriate marketing policies in extra production, reducing cost of production, diversifying farming and cropping system, promoting secondary agriculture and value addition, and augmenting income from other sources. Action plan for up scaling technologies, capacity building and strengthening of marketing is discussed here to achieve the solemn goal of doubling farmers’ income by 2022 in Rajasthan.